A perceptual computing-based approach for peer assessment - Kok, Chin Chai; Tay, Kai Meng (IEEE, 2014)
Peer assessment is useful for assessing an individual's contribution in a collaborative learning task. It is commonly used in institutions of higher education as normally each class has a large number of students. Peer assessment allows students to assess their group members' contributions. It also helps the instructor to arrive at an assessment that reflects individual's effort in a collaborative learning task. In this paper, a perceptual computing (Per-C)-based peer assessment procedure is investigated. The assessment adopts vague and imprecise words in the evaluation process. Per-C is selected because it allows uncertainties of words to be considered in the decision making process. A real case study is conducted to demonstrate the effectiveness of the proposed method. The results show that the use of Per-C in peer assessment is important.